Screening for Methylmalonic and Propionic Acidemia: Clinical Outcomes and Follow-Up Recommendations - Patrice K. Held; Emily Singh; Jessica Scott Schwoerer (MDPI AG, 2022)
Wisconsin's newborn screening program implemented second-tier testing on specimens with elevated propionylcarnitine (C3) to aid in the identification of newborns with propionic and methylmalonic acidemias. The differential diagnosis for elevated C3 also includes acquired vitamin B12 deficiency, which is currently categorized as a false positive screen. The goal of this study was to summarize screening data and evaluate their effectiveness at establishing diagnoses and categorizing false positive cases. All Wisconsin newborns born between 2013 and 2019 with a positive first-tier screen for C3 were included in this study. For each case the first- and second-tier newborn screening data and confirmatory test results were compiled. The clinical determination for each case was reviewed and categorized into groups: inborn error of metabolism, maternal B12 deficiency, infant B12 deficiency, and false positive. A review of the screening data showed a significant overlap in the concentration of biomarkers for newborns with genetic versus acquired disease. Additionally, a review of confirmatory test results showed incomplete ascertainment of maternal vitamin B12 status. The Wisconsin newborn screening program recommended a confirmatory testing algorithm to aid in the diagnosis of inborn errors of metabolism and acquired vitamin B12 deficiency.